The impact of cannabis use on ageing and longevity: a systematic review of research insights - Sonam Nain; Niraj Singh; Anne Katrin Schlag; Michael Barnes (Journal of Cannabis Research)
Abstract Background With aging emerging as a global challenge linked to chronic diseases, identifying interventions that support a healthy lifespan and health span has become imperative. Cannabinoids derived from cannabis, particularly cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC), have gained attention for their potential to promote healthy aging through interactions with the endocannabinoid system. While CBD has often been highlighted for its benefits, emerging evidence indicates that THC, under certain conditions and doses, may also play a therapeutic role in aging. Despite this interest, significant knowledge gaps persist in understanding cannabis’s role in promoting healthy aging and longevity. Aim We reviewed recent literature to investigate the effect of cannabinoid use, particularly CBD and THC on aging and longevity. By synthesizing findings from preclinical models, clinical studies, and real-world evidence, we aimed to elucidate the potential of cannabinoids, in fostering healthy aging, mitigate age-related decline, and promote well-being in older populations. Method We conducted a systematic review guided by PRISMA to investigate the impact of cannabinoids on aging and longevity. Studies involving preclinical models (e.g., Caenorhabditis elegans, rodents, zebrafish, and mice) and clinical populations aged 50 years and older were included. Exclusion criteria targeted acute effects and mechanisms of action in different medical conditions. Aging was explicitly defined as biological and psychological changes associated with advancing age, and longevity was defined as the extension of lifespan and factors influencing healthy aging. Findings Eighteen studies investigating the direct impact of cannabinoids on aging and longevity were identified in preclinical models (11) and human studies (7). Preclinical studies have shown promising results regarding the potential benefits of cannabinoids including improved lifespan, cognitive function, inflammation, memory, sleep quality, and social interaction. The effects of THC appear more complex, with potential benefits at low doses and drawbacks at higher doses, highlighting their complex role in aging. However, the limited number of human studies hinders a comprehensive understanding. Clinical studies also suggest potential therapeutic applications for cannabinoids in aging populations, although further research is needed to understand their mechanisms of action and long-term effects fully. Conclusion Cannabinoids hold promise for supporting healthy aging and enhancing the quality of life in older populations. While preliminary research suggests intriguing possibilities, more studies are needed to solidify the link between cannabis use, the ECS, and healthy aging in humans. Rigorous clinical trials are crucial to evaluate their safety and efficacy. Longitudinal studies and well-designed clinical trials are critical to understanding the safety, efficacy, and long-term effects of cannabis use in aging populations. Future research should optimize dosages, investigate mechanisms of action, and explore the influence of cannabis use initiated in aging as opposed to lifetime exposure. Clarifying these aspects is vital for informing public health strategies and developing targeted therapeutic interventions for age-related conditions.